2016
DOI: 10.1021/acs.jpcb.6b08480
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Mechanism of Phosphomevalonate Kinase: Implications for Rational Engineering of Isoprenoid Biosynthetic Pathway Enzymes

Abstract: Mevalonate pathway is of important clinical, pharmaceutical and biotechnological relevance.However, lack of the understanding of the phosphorylation mechanism of the kinases in this pathway has limited rationally engineering the kinases in industry. Here the phosphorylation reaction mechanism of a representative kinase in the mevalonate pathway, phosphomevalonate kinase, was studied by using molecular dynamics and hybrid QM/MM methods. We find that a conserved residue (Ser106) is reorientated to anchor ATP via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Previously the catalytic mechanism of PMK, a GHMP kinase in the mevalonate pathway, was revealed using a combined QM/MM study. 5 It was found that reaction occurred via a direct phosphorylation mechanism and a positively charged residue, Lys101, stabilizes the negative charge at the cleaved β-,γ-bridging oxygen of ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Previously the catalytic mechanism of PMK, a GHMP kinase in the mevalonate pathway, was revealed using a combined QM/MM study. 5 It was found that reaction occurred via a direct phosphorylation mechanism and a positively charged residue, Lys101, stabilizes the negative charge at the cleaved β-,γ-bridging oxygen of ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Arg241 plays a pivotal role in organizing the highly flexible triphosphate tail of ATP, as well as neutralizing the negative charge accumulated at the β-,γ-bridging oxygen of ATP during phosphate transfer. Thus far, MVK, GALK 22 and PMK 23 have all been shown through QM/MM studies to have an inline, direct phosphate transfer mechanism instead of a catalytic base mechanism. Homoserine kinase, which lacks such potential catalytic base residue in the active site would also function through direct phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, QM/MM studies on GHMP kinases galactokinase (GALK) 22 and phosphomevalonate kinase (PMK) 23 revealed that these enzymes actually function through a direct phosphorylation mechanism. Thus it is necessary to resolve the uncertainty around the mechanism of MVK, a representative GHMP kinase that was conventionally deems to catalyse the phosphorylation via the catalytic base mechanism.…”
Section: Phosphorylation Mechanism Of Mvkmentioning
confidence: 99%
See 2 more Smart Citations